PENGARUH IKLIM ORGANISASI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH MENENGAH ATAS (SMA) ABDUSSALAM - B31110152, M. Basri (Jurnal Manajemen Update, 2016)
One that determine whether good or not an organization is that from Organizational Climate and its leadership. Therefore, employees will feel more loyal and responsible in carrying out the task. It is shown in Abdussalam high school, teachers felt there was a gap between organizational Climate and its principal leadership. This research aims to test the influence of Climatic factors of the Organization, the principal leadership, towards teachers performance.Â The research sample took 1 school and 30 teachers on the education sector. The sampling is sampling. Data analysis using multiple regression test analysis tools that are preceded by a classic assumption test which consist of normality test, multicollinearity test, test heteroskedastisitas multicollinearity and linierity test. Hypothesis testing is done using the F-test and t-test with significance level Î± = 0.05.Â The results of partial test from each variable showed that the variables of the climate of the Organization and principal leadership did not influence significantly to the performance or have a negative influence. Simultaneous test results showed that all the independent variables have no effect on performance significantly. Keywords: climate, leadership, performance, teacher